Impacts of palatal coverage on bolus formation during mastication and swallowing and subsequent adaptive changes. (9th August 2013) - Sato, T.; Furuya, J.; Tamada, Y.; Kondo, H.
Summary Palatal coverage is often required for elderly edentulous patients with complete dentures. The purpose of this study was to clarify impacts of palatal coverage on bolus formation and subsequent adaptive changes. Subjects were 18 healthy young dentulous adults who wore 1·5‐mm‐thick palatal plates. Subjects were asked to feed 12 g of bicoloured rice as usual, and the bolus formation by mastication and swallowing in the pharynx was observed using a nasal videoendoscopy. The bolus formation index (BFI), number of mastication strokes until swallowing, visual analogue scale about swallowing easiness and masticatory performance using colour‐changeable gum were measured under three conditions: before placement of the palatal plate (day 0), immediately after placement (day 1) and after 7 days of wearing the plate (day 7). BFI and visual analogue scale on day 1 were significantly lower than those on day 0, but those on day 7 significantly recovered to the level of day 0. The number of mastication strokes did not change from day 0 to day 1, however, that on day 7 was significantly higher. Masticatory performance on days 1 and 7 was significantly lower than that on day 0. Although palatal coverage inhibits bolus formation during feeding, subjects increased the number of mastication strokes until swallowing threshold as they adapted to palatal coverage over time. This adaptive change was due to compensate for the lowered masticatory performance to achieve bolus formation for comfortable swallowing.